Detection of Human Parvovirus 19 in People with Beta Thalassemia Major (the City of Diwaninah) (Open Herald: Periodical of Methodical Research, 2026)
study samples were collected at Diwaniyah Teaching Hospital / Hematology Center in Diwaniyah city for the period from 1 November 2023 to 1 February 2024. This study aimed to detect the spread of the Parvovirus B19 virus among patients with Thalassemia beta major type. The study included 85 samples from both sexes and different age groups. The samples were divided into two groups: the first included patients with Thalassemia beta major type, and included 72 samples, and the second included the control group (healthy people) and included 13 samples. Blood samples were collected for the study groups of patients visiting the Hematology Center, and the linear polymerase chain reaction technique was used to detect viral DNA,